Reviews on biomarker studies of metabolic and metabolism-related disorders - Guest, Paul C. (Advances in experimental medicine and biology, 2019)
1. Insulin Resistance in Schizophrenia -- 2. Biogenesis of the Insulin Secretory Granule in Health and Disease -- 3. Current Models of Fatty Liver Disease; New Insights, Therapeutic Targets and Interventions -- 4. Preclinical Models of Altered Early Life Nutrition and Development of Reproductive Disorders in Female Offspring -- 5. Targeting Mitochondrial Defects to Increase Lngevity in Animal Models of Neurodegenerative Diseases -- 6. Computational Approaches for Identification of Pleiotropic Biomarker Profiles in Psychiatry -- 7. MiRNA Regulation of Glucose and Lipid Metabolism in Relation to Diabetes and Non-Alcoholic Fatty Liver Disease -- 8. Hypercaloric Diet-Induced Obesity and Obesity-Related Metabolic Disorders in Experimental Models -- 9. Metabolic Biomarkers in Nematode C. elegans During Aging -- 10. Circular RNAs as potential biomarkers and therapeutic targets for metabolic diseases -- 11. Deciphering Endothelial Dysfunction in the HIV-Infected Population -- 12. The Role of Inflammation in the Development of GDM and The Use of Markers of Inflammation in GDM Screening -- 13. PFKP Signaling at a Glance: an Emerging Mediator of Cancer Cell Metabolism -- 14. ATAD3A on the Path to Cancer -- 15. Impact of Exercise on Inflammatory Mediators of Metabolic and Vascular Insulin Resistance in Type 2 Diabetes